Nutritional composition of three varieties of sweet potato (Ipomea batata L.) based diet commonly consumed in Nigeria: a comparative study - Seun F. Akomolafe (Food Chemistry Advances)
Sweet potatoes are widely consumed due to their rich nutritional composition and health benefits. This study analyzed and compared the nutritional compositions of diets formulated from three sweet potato varieties—orange-fleshed (OFSP), purple-peel-white-fleshed (PPWSP), and white-peel-white-fleshed (WPWSP). Standard analytical methods were used to determine proximate composition, vitamin content, fatty acid profiles, amino acid composition, and estimated glycaemic index (eGI). OFSP diet had the highest crude protein, fat, ash, moisture, fiber, and vitamins A, D, C, and B6. Vitamin K and B1 were consistently low in all samples. PPWSP diet contained the highest polyunsaturated fatty acids (PUFA), especially linoleic acid (C18:2 cis-9,12), and the highest saturated fatty acid (SFA) content. OFSP had the highest total amino acid content (93.35 g/100 g), while WPWSP exhibited the highest starch content (70.40 mg/100 g) and the lowest total carbohydrate (85.97%). All diets had a low eGI, making them suitable for diabetes management. Overall, each variety provides distinct nutritional benefits, with OFSP excelling in vitamins and amino acids, PPWSP in PUFA, and WPWSP in carbohydrates. These findings highlight the potential of sweet potato-based diets in promoting health and managing blood sugar levels.